2019
DOI: 10.1002/imhj.21829
|View full text |Cite
|
Sign up to set email alerts
|

Male callers to an Australian perinatal depression and anxiety help line—Understanding issues and concerns

Abstract: We would like to thank the Perinatal Anxiety and Depression Australia (PANDA) national helpline for providing the de-identified data for analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Most of the findings reported to date have focused on the experience of mothers. The role of fathers in fostering healthy attachment with the infant to support developmental outcomes for infants is also important 13,14 More recent findings indicate that fathers of babies admitted to NICU experience symptoms of trauma, depression and anxiety 9,10,15 . A meta‐analysis review of paternal depression identified rates of up to 10.4% over the perinatal period with higher rates 3‐6 months postpartum 16 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the findings reported to date have focused on the experience of mothers. The role of fathers in fostering healthy attachment with the infant to support developmental outcomes for infants is also important 13,14 More recent findings indicate that fathers of babies admitted to NICU experience symptoms of trauma, depression and anxiety 9,10,15 . A meta‐analysis review of paternal depression identified rates of up to 10.4% over the perinatal period with higher rates 3‐6 months postpartum 16 .…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis review of paternal depression identified rates of up to 10.4% over the perinatal period with higher rates 3‐6 months postpartum 16 . NICU mothers and fathers also report a higher likelihood of depression when there is relationship distress, 10 with relationship breakdown being cited as a reason for fathers contacting perinatal helplines for mental health support 15 . However, research examining the experience of fathers in NICU settings is in its infancy and no study has examined the experience of fathers drawn from regional and remote communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a sample of 102 men who had experienced a stressful life event, a moderate correlation was reported between depression and externalizing (r = 0.32) indicated by 11 items including having a "short fuse, " punching something, or yelling at someone. Importantly, it is not that women do not experience anger in the context of depression because research indicates they do (40,46). Instead, the contention is that observable symptoms align with gender-based socialized expectancies whereas current diagnostic criteria and screening instruments are weighted toward to female symptom presentations (33,44).…”
Section: Introductionmentioning
confidence: 99%
“…The programme has demonstrated high acceptability among fathers including those with high levels of distress. 9 The messages from SMS4dads were tailored to partners of mothers with SMI by a team of clinicians and researchers with experience in identifying fathers' needs and the treatment of new mothers with SMI. 10 One aim of the current study was to assess the acceptability and perceived usefulness of messaging for partners of mothers with SMI.…”
mentioning
confidence: 99%